Improving Sociology at Tribhuvan University: A Deliberation with Suggestions - Mishra, Chaitanya (Nepal Journal of Sociology, 2025)
This essay serves as both a reflective piece and a commentary, weaving together my observations and experiences emanating from my long engagement with the Central Department of Sociology at Tribhuvan University (TU). The comments outlined here emerge from a series of formal and informal interactions with colleagues within the department and university, rather than relying on any hard data. Hence, this needs to be understood as my process of retrospection and introspection, which are essential for reappraising institutional realities and requisite reforms. There is no claim here that there was a golden age at some point during the 45-year history of Sociology at TU. Nonetheless, the downslide is dated roughly to the 2006-2007 national political transition, which led to a powerful regime of unionization among teachers, administrators and students that, in turn, has led to normlessness as well as a serious loss of professional and managerial standards at TU. Choosing a suggestive stand, I mark the swift decline in the quality of teaching and learning in the discipline of Sociology at TU and propose the necessary reforms that the Sociology Subject Committee, along with various Departments of Sociology within TU, ought to realize to take corrective actions to improve teaching and research in Sociology.